Plasma interleukin 6 as an outcome predictor of traumatic brain injury patients - Ichwan, Khairunnisa; Gazali, Syahrul; Suherman, Suherman; Desiana, Desiana; Nurjannah, Nurjannah (Narra Sains Indonesia, 2023)
Traumatic brain injury is one of the leading causes of death and disability in young adults. Previous studies have suggested that neuroinflammatory process involves the overexpression of interleukin 6 (IL-6); however, data on the predictive ability of IL-6 is limited and conflicting in traumatic head injury patients. The aim of this study was to assess the ability of plasma IL-6 as a predictor of outcome in head injury patients. A cross-sectional study was conducted between June and December 2020 among traumatic head injury patients admitted to Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia. Demographic, clinical data, and IL-6 level were collected and measured on admission. The outcome was assessed by the Glasgow outcome scale extended (GOSE) in the first- and third-month of post-injury. A total of 50 traumatic brain injury patients were recruited of which 54% were male, 64% had mild head injury, 82% had leukocytosis, and 60% had non-bleeding head CT scan. The mean of IL-6 level was 79.32 pg/mL while the GOSE scores ranged from 1 (death) to 8 (upper good recovery). Early IL-6 level (<24 hours post-injury) was significantly correlated with worse outcome in traumatic head injury, though the correlation strength was moderate (p<0.001; r=-0.42). As a predictor, IL-6 yielded the area under curve (AUC) value of 93.5% (p<0.001) and a cut-off point of 46.33 pg/mL. The sensitivity and specificity of this predictor were 87.5% and 95.24%, respectively. In conclusion, early IL-6 level can be used as a predictor for traumatic head injury. Nevertheless, further multi-center study with a bigger sample size is needed to confirm this finding.